2016
DOI: 10.1016/j.molcel.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Uncoupling of DNA Double Strand Break Repair Pathways within Mammalian Heterochromatin

Abstract: Repetitive DNA is packaged into heterochromatin to maintain its integrity. We use CRISPR/Cas9 to induce DSBs in different mammalian heterochromatin structures. We demonstrate that in pericentric heterochromatin, DSBs are positionally stable in G1 and recruit NHEJ factors. In S/G2, DSBs are resected and relocate to the periphery of heterochromatin, where they are retained by RAD51. This is independent of chromatin relaxation but requires end resection and RAD51 exclusion from the core. DSBs that fail to relocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
317
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(343 citation statements)
references
References 41 publications
20
317
5
1
Order By: Relevance
“…It was proposed that the methylation of H3K9 in these repetitive regions might sequester damage away from the HR machinery, thus reducing the risk of inappropriate repair. Consistently, the groups of Karpen (Chiolo et al 2011;Janssen et al 2016), Chiolo (Ryu et al 2015), and Soutoglou (Tsouroula et al 2016) found that breaks within heterochromatic sequences were repaired differently than breaks in euchromatin, at least when it came to HR. They described an HP1a-dependent pathway for repair in heterochromatin (Chiolo et al 2011) that allows early steps of the DNA damage response to occur, but then ensures that later steps (i.e., Rad51 binding) occurred only after the break site had been relocated outside of the heterochromatic domain.…”
Section: Rna:dna Hybrids: Transcription Intermediates Impair Replicatmentioning
confidence: 71%
“…It was proposed that the methylation of H3K9 in these repetitive regions might sequester damage away from the HR machinery, thus reducing the risk of inappropriate repair. Consistently, the groups of Karpen (Chiolo et al 2011;Janssen et al 2016), Chiolo (Ryu et al 2015), and Soutoglou (Tsouroula et al 2016) found that breaks within heterochromatic sequences were repaired differently than breaks in euchromatin, at least when it came to HR. They described an HP1a-dependent pathway for repair in heterochromatin (Chiolo et al 2011) that allows early steps of the DNA damage response to occur, but then ensures that later steps (i.e., Rad51 binding) occurred only after the break site had been relocated outside of the heterochromatic domain.…”
Section: Rna:dna Hybrids: Transcription Intermediates Impair Replicatmentioning
confidence: 71%
“…DSB and global genome-induced mobility can eventually favour timely encounter. C The limitation of resection progression by a compact chromatin structure can provide the time for the moving DSB to find the homologous donor and allow a productive homology search prior Rad51 binding Tsouroula et al 2016). It is likely that the spatial separation between DNA end resection and homology search prevents illegitimate HR between repeats of different chromosomes that cluster in these domains.…”
Section: Limiting Resection In Heterochromatin: What Functional Consementioning
confidence: 99%
“…HRR may sometimes be suppressed within repetitive DNA units if the damaged DNA side is not relocated to the heterochromatin periphery. In these cases, single-strand annealing (SSA) takes place instead [14]. It has also been shown that especially in cases of irradiation at higher doses (>2 Gy) and consequently more DBSs, the conventional NHEJ (c-NHEJ) may fail at some breakage sites and an alternative NHEJ process (a-NHEJ) is applied, which is a slow and error-prone repair process [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the densely packed heterochromatin because the damaged DNA has to be histone free for the repair and must also be accessible for the repair protein complexes [46,47,48]. It has been shown that DSBs in the heterochromatin region are usually be repaired at the border of heterochromatic chromatin regions [1,2,14,49] whereby the methylation degree typical for heterochromatin remains unchanged. Re-organization within heterochromatic regions is necessary to make the damage accessible for repair proteins.…”
Section: Introductionmentioning
confidence: 99%